The Fate of Foodborne Pathogens in Manure Treated Soil - Black, Zoe; Balta, Igori; Black, Lisa; Naughton, Patrick J.; Dooley, James S. G.; Corcionivoschi, Nicolae (Frontiers in Microbiology, 2021)
The aim of this review was to provide an update on the complex relationship between manure application, altered pathogen levels and antibiotic resistance. This is necessary to protect health and improve the sustainability of this major farming practice in agricultural systems based on high levels of manure production. It is important to consider soil health in relation to environment and land management practices in the context of the soil microflora and the introduction of pathogens on the health of the soil microbiome. Viable pathogens in manure spread on agricultural land may be distributed by leaching, surface run-off, water source contamination and contaminated crop removal. Thus it is important to understand how multiple pathogens can persist in manures and on soil at farm-scale and how crops produced under these conditions could be a potential transfer route for zoonotic pathogens. The management of pathogen load within livestock manure is a potential mechanism for the reduction and prevention of outbreaks infection with Escherichia coli, Listeria Salmonella and Campylobacter. The ability of Campylobacter, E. coli, Listeria and Salmonella to combat environmental stress coupled with their survival on food crops and vegetables post-harvest emphasizes the need for further study of these pathogens along with the emerging pathogen Providencia given its link to disease in the immunocompromised and its’ high levels of antibiotic resistance. The management of pathogen load within livestock manure has been widely recognized as a potential mechanism for the reduction and prevention of outbreaks infection but any studies undertaken should be considered as region specific due to the variable nature of the factors influencing pathogen content and survival in manures and soil. Mediocre soils that require nutrients could be one template for research on manure inputs and their influence on soil health and on pathogen survival on grassland and in food crops.